The Role of Organizational Trust on the Influence of Employer Branding on Employee Performance - Ekhsan, Muhamad; Saroh, Tim (International Journal of Management Science and Information Technology, 2021)
Employer branding is a concept that can be applied within a company to make employees feel comfortable and feel that the company is a good place to work. The goal of employer branding is for the new employee selection process to make it easier to find the best candidates and retain existing employees. By utilizing employer branding, the company will be better in the eyes of employees as well as there will be many prospective new employees who are interested in working at the company. The purpose of this study was to determine the effect of employer branding on employee performance mediated by organizational trust. This study used 95 respondents as the sample. The instrument testing method uses the SmartPLS. The results of this study are employer branding has a significant effect on employee performance, employer branding has a significant effect on organizational trust, organizational trust has a significant effect on employee performance, Organizational trust is able to mediate employer branding influence on employee performance.